Larangan Hakim Menangani Perkara Dalam Keadaan Marah - Bariek Ramdhani Pababbari; Laode Ismail; Abdul Rahman Sakka (Pledoi Law Jurnal, 2024)
ABSTRACT: A judge becomes very vulnerable to various irregularities, whether done intentionally, for example deciding someone is guilty and then being justified only because he gave money to the judge or done accidentally, for example deciding someone who is innocent because the evidence shows that. Everything will be held accountable before Allah SWT. For this reason, the position of judge receives special attention, among other things in positive law, this can be seen from the existence of basic judicial laws which specifically regulate judicial procedures, including the position of judge. Not only in positive law in Islamic law, the position of judge also receives special attention, with verses from the Koran discussing the position of judge even long before positive law regulates it. A judge is someone who exercises judicial power as regulated by law, someone who decides a case fairly based on evidence and his own beliefs. In exercising judicial power, judges are faced with various things that can influence theirdecisions later. Thus, the position of judge is very important because deciding a case is not an easy thing. He must be very careful in imposing punishment on the guilty because the guilty are sometimes justified. ABSTRAK: Seorang hakim menjadi sangat rentan akan berbagai penyimpangan akan berbagai penyimpangan baik yang dilakukan secara sengaja misalnya memutus seseorang yang bersalah kemudian dibenarkan hanya karena memberikan uang kepada hakim tersebut ataupun yang dilakukannya secara tidak sengaja misalnya memutus seseorang yang tidak bersalah karena bukti-bukti yang menunjukan demikian. Segala sesuatunya akan dipertanggung jawabkan dihadapan Allah SWT. Oleh sebab itu jabatan hakim mendapat perhatian khusus, antara lain dalam hukum positif terlihat dengan adanya undang- undang pokok kehakiman yang secara khusus mengatur tata cara peradilan termasuk jabatan hakim. Tak hanya dalam hukum positif dalam hukum Islam pun jabatan hakim mendapat perhatian khusus dengan ayat-ayat Al-Qur’an yang membahas tentang jabatan hakim ini bahkan jauh sebelum hukum positif mengaturnya. Hakim adalah seseorang yang melakukan kekuasaan kehakiman yang diatur menurut undangundang, seseorang yang memutus suatu perkara secara adil berdasar atas bukti-bukti dan keyakinan yang ada pada dirinya sendiri. Dalam melakukan kekuasaan kehakiman hakim dihadapkan dengan berbagai hal yang dapat mempengaruhi putusannya nanti. Dengan demikian jabatan hakim ini menjadi sangat penting karena memutus suatu perkara bukanlah hal mudah. Ia harus sangat berhati-hati menjatuhkan hukuman kepada yang bersalah sebab yang bersalah kadang-kadang dibenarkan.